Annexin II as a dengue virus serotype 2 interacting protein mediating virus interaction on Vero cells - Aliyu, Isah Abubakar; Ling, King Hwa; Md Hashim, Nur Fariesha; Lam, Jia Yong; Chee, Hui Yee (MDPI, 2019)
Recent evidence has demonstrated that dengue virus requires active filopodia formation for a successful infection. However, the cellular factor involved in the interaction has not been fully elucidated. We used a combination of virus overlay protein binding assay and LC-MS/MS, and identified annexin II as a dengue virus serotype 2 (DENV2) interacting protein on Vero cells, upon filopodia induction. Flow cytometry analysis showed annexin II on the Vero cells surface increased when DENV2 was added. The amount of annexin II in the plasma membrane fraction was reduced as the infection progressed. Antibody-mediated inhibition of infection and siRNA-mediated knockdown of annexin II expression significantly reduced DENV2 infection and production levels. Collectively, we demonstrated that annexin II is one of the host factor involved in DENV2 binding on Vero cells.